2021
DOI: 10.1038/s41598-021-81669-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel myostatin-specific antibody enhances muscle strength in muscle disease models

Abstract: Myostatin, a member of the transforming growth factor-β superfamily, is an attractive target for muscle disease therapy because of its role as a negative regulator of muscle growth and strength. Here, we describe a novel antibody therapeutic approach that maximizes the potential of myostatin-targeted therapy. We generated an antibody, GYM329, that specifically binds the latent form of myostatin and inhibits its activation. Additionally, via “sweeping antibody technology”, GYM329 reduces or “sweeps” myostatin i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
(91 reference statements)
0
21
0
Order By: Relevance
“… 27 Latent myostatin is reported to be cleaved by proteases and produce mature myostatin. 29–31 To evaluate the effect of Fc engineering on antigen clearance, we need to measure not only latent myostatin concentration in plasma, but also that of mature myostatin. Therefore, we measured total myostatin concentration (mature + latent myostatin) in plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Latent myostatin is reported to be cleaved by proteases and produce mature myostatin. 29–31 To evaluate the effect of Fc engineering on antigen clearance, we need to measure not only latent myostatin concentration in plasma, but also that of mature myostatin. Therefore, we measured total myostatin concentration (mature + latent myostatin) in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant latent myostatin and anti-latent myostatin antibodies were prepared by the method described previously. 29 For the preparation of FcγRs, the genes encoding the extracellular region of human and cynomolgus FcγRs were synthesized based on the sequence information obtained from the National Center for Biotechnology Information or from the results of cDNA cloning conducted in house, respectively. FcγRs were fused with His-tag at their C-terminus.…”
Section: Methodsmentioning
confidence: 99%
“…Myostatin-specific antibody can be promising in LC patients. It can improve muscle strength [ 61 ]. It was reported that vitamin D receptors are expressed in skeletal muscle cells, suggesting that vitamin D may have a direct effect on skeletal muscle [ 62 ].…”
Section: Intervention For Lc Patients With Sarcopeniamentioning
confidence: 99%
“…Myostatin (MSTN) is an important member of transforming growth factor superfamily, also known as growth differentiation factor-8 (GDF-8), which is mainly manifested in the negative regulation of muscle growth and strength increase (58). MSTN can activate receptor function by binding to ALK4/5 and ActR2A/B type receptors on the surface of muscle cells, and lead to the function of promoting protein degradation and inhibiting protein synthesis in muscle (59). Specifically, the mature MSTN fragment first binds to type II receptor (mainly ActRIIB) and starts the signal cascade in muscle cells, which makes ActRIIB autophosphorylate and bind to type I receptor (ALK4 and ALK5) with low affinity to enhance the transcription process of target gene (60).…”
Section: Guanidinoacetic Acid Regulates Genes Involved In Skeletal Muscle Developmentmentioning
confidence: 99%